Effects Study of Some Common Food Additives on Histological and Functional Thyroid Gland in Young Male Albino Rats - Sarmad A. Abbas, Hussein A. Al-Hamadawi (Pakistan Journal of Medical & Health Sciences, 2022)
The current study was conducted in the animal house / Department of biology / Al- University of Qadisiyah from November to February This is for the purpose of studying the effect of some food additives on the histological structure and function of the thyroid gland, as well as some oxidative indicators. The current study included 32 young male albino rats randomly distributed into four equal groups The control dosed 1 ml of normal drinking water during the 30-day trial period, the first treatment group (T1) Tetrazine was dosed at a concentration of 25 mg/kg body weight for the duration of the 30-day trial period, The second treatment group (T2) received a chocolate brown dye at a concentration of 200 mg/kg body weight for the duration of the 30-day trial, The third treatment group (T3) dosed the preservative sodium benzoate at a concentration of 50 mg/kg body weight for the duration of the 30-day trial. The results of the statistical analysis showed a significant decrease in the concentration of Thyroxine T4, Thyroid Stimulating Hormone(TSH), enzyme concentration level Superoxide dismutases )SOD(, and Significant increase in the level of concentration of malondidehyde (MDA) In the first group ) T1( and the second group (T2) Compared with the control group. The results also showed a significant increase in (MDA) A significant decrease in the level of (SOD) in a group (T3) Compared with the control group, there was no significant difference in the concentration of T4 & TSH in a group (T3) compared to the control group. The histological study also showed that pathological histological changes occurred in (T1) (T2) )T3) Represented by changing the diameter of the thyroid gland’s follicles and colloids Where there are many small irregular thyroid follicles, as well as bubbles in the colloidal substance And the occurrence of hyperplasia and an increase in the thickness of the lining layer of the vesicles. We conclude from the current study that eating food additives causes some negative on the histological structure and function of the thyroid gland. Keywords: Thyroid gland ,Tartrazine, Chocolate Brown HT E155, Benzoat sodium.